Research on the Enhancement of an Anammox System Using Iron Derived from Excess Sludge - Zhao, Yuhe; Ning, Xinqiang (International Journal of Natural Resources and Environmental Studies, 2026)
This study uses iron recovered from excess sludge to enhance an anammox system. Results show that sludge‑derived iron significantly improves nitrogen removal efficiency, optimizes extracellular polymeric substances (EPS) composition, and increases heme c content to strengthen microbial activity. Microbial analysis reveals that iron selectively enriches anammox functional bacteria. The reactor with K1 carrier performs best. This approach realizes sludge resource utilization and enhances anammox process, achieving waste treatment by waste.